Tantangan dan Strategi Guru dalam Mengatasi Problematika Pengelolaan Kelas pada Madrasah Ibtidaiyah - Winarno, Dwi; Mujahid, Kasori (TSAQOFAH, 2024)
This research aims to explore various problems faced by teachers in the context of classroom management and explore strategies that can be used to overcome these challenges. The data collection method was carried out by interviewing teachers from grade level and involving direct observation in the classroom environment. Some of the problems that arise include challenges in managing student behavior, difficulties in adapting teaching methods to diverse learning styles, as well as practical obstacles such as limited resources and classroom space. In response to these problems, this research presents a number of practical strategies that can be implemented by teachers, to increase interaction in the classroom, the application of student-centered teaching methods, and collaborative efforts between teachers and parents. Additionally, it emphasized the need for increased administrative support and ongoing training opportunities for teachers. The results of this research provide an in-depth picture of the complexity and diversity of challenges faced by teachers in classroom management. By presenting strategies that can be implemented, this research contributes to a practical and sustainable understanding of efforts to increase the effectiveness of teachers' classroom management amidst the dynamics of contemporary education.